A New Approach to the Interpretation of Signals from Temperature Sensors - Blagojevic, Milan; Petkovic, Dejan (Communications - Scientific letters of the University of Zilina, 2006)
A basic approach in adaptive modeling of data acquisition is based on the comparison of real time data with the data previously predicted from the adequate numerical model. Our research was initiated to find a better algorithm for prediction of fire growth in enclosed spaces by means of interpretation of signals from fire sensors. The data obtained from temperature sensors are compared in a real time with predicted data and are used to adjust the numerical model for prediction so that it matches the reality. This adaptive approach has the following primary goals: early warning of fire growth, better alarm decision making, realization of an adaptive threshold (a threshold changing in the time according to the input signal), very small false alarm rate, etc. In this paper we introduce a method that uses smooth spline polynomials for approximation of the collected data and the time sliding window principle. The length of time sliding window varies in the real time and depends on the calculated error.